RESPONSE OF IAIN KERINCI STUDENTS (FACULTY OF SHARIA) REGARDING THE DISTRIBUTION OF INHERITANCE ACCORDING TO ISLAMIC LAW - Alzaki Epriandi Alzaki; Mursal mursal (UIN Mahmud Yunus Batusangkar, 2024)
The aim of the research is to obtain an overview of inheritance distribution in Islamic law and customary law, as well as to understand the students' responses regarding the application of Islamic law and customary law in the distribution of inheritance. The research method used in this study is a descriptive quantitative approach, also known as empirical research. This research focuses on the correlation between the factors being studied and uses data obtained from surveys or the assistance of Google Forms with quota sampling or random sampling methods. The number of respondents involved in this research is 54 respondents with 13 questions. The results of the study indicate that most respondents have sufficient knowledge about the law of inheritance distribution in Islam, but there are also some respondents who are neutral or disagree. Regarding the understanding of the content of inheritance distribution law in Islam, most respondents agree that the law aligns with the principle of justice. However, there are also some respondents who are neutral or disagree with this statement. The research method used in this study is a descriptive quantitative approach or empirical research with survey data or the assistance of Google Forms with quota sampling or random sampling methods.